Keanekaragaman Jenis Vegetasi Strata Herba di Bukit Gatan Kabupaten Musi Rawas - Eva Kusuma; Merti Triyanti; Sepriyaningsih Sepriyaningsih (Jurnal Biologi Papua, 2021)
This study aims to determine the Importance Value Index (INP), Vegetation Diversity Index, and abiotic factors in herbal strata in Bukit Gatan, Musi Rawas Regency. Determination of Herbs Strata Vegetation Diversity in Bukit Gatan Musi Rawas Regency using the point intercept method, which uses herbal touch rods that are below the touch point line. This research was made into 3 research study areas, namely study area A (1-10 stands), study area B (1-10 stands) and study area C (1-10 stands), then the data were analyzed descriptively quantitative. the highest importance index (INP) has been conducted in the study area A, the caladium (Caladium sp) of 50.33%, the study area B is the arrowroot (Maranta arundiciae) plant at 69%, and in the study area C is the bandotan plant (bandotan plant) Ageratum conyzoidez) by 39%. The average diversity of the Study Area A diversity index was 0.55, Study area B was 0.26 and Study area C was 0.33. Abiotic factors in the Bukit Gatan Region, Musi Rawas Regency, greatly affect the life of herbaceous strata in the Bukit Gatan Forest Area, Musi Rawas Regency. The air temperature in the gatan hill protection forest area ranges (28.30C) with soil moisture (15) while the humidity ranges (92.6%) while the soil temperature ranges (27.10C) and soil pH ranges (6.6).